Menghidupi Injil di Tepian: Penguatan Spiritual dan Sosial bagi Yayasan Kasih-Kasihan - Renson Siahaan; Timotius Mangiring Tua; Jabes Pasaribu; Oniaman Buulolo; Mega Riana (Journal Of Social Empowerment Publications, 2025)
Mental health issues in Indonesia continue to face social stigma, limited services, and a lack of attention toward the community of People with Mental Disorders (ODGJ). This Community Service Program (PkM) was conducted by lecturers and students of the Bachelor of Theology Program at Sekolah Tinggi Teologi Real Batam at the Kasih-Kasihan Foundation, Batam. The purpose of this activity is to strengthen spiritual and social awareness toward marginalized groups through a loving service approach. The method employed is descriptive qualitative, utilizing direct observation, short worship, reflective discussion, and the provision of basic assistance. The results indicate that an approach rooted in love and acceptance can restore participants’ dignity, self-confidence, and hope for life. This activity affirms the role of theological institutions in implementing the Gospel contextually among “edge communities” and demonstrates that inclusive spiritual service can serve as a means of holistic recovery for people with mental disorders.